Transnational business collaboration among Common Market countries: its implication for political integration - Feld, Werner J. (New York : Praeger, 1970)
The idea of this book was born when the European Economic Community (EEC), or Common Market, found itself in a period of abject stagnation following the 1965 crisis provoked by President Charles De Gaulle, whose intent was to emasculate whatever progress had been made in the realm of political integration
Bibliography: p. [131]-139.
osc 14/11/2018
Loans
Keywords: Common Markets